2020
DOI: 10.5820/aian.2701.2020.86
|View full text |Cite
|
Sign up to set email alerts
|

The Culture is Prevention Project: Measuring Culture As a Social Determinant of Mental Health for Native/Indigenous Peoples

Abstract: Programs serving American Indian (AI) youth are an important component of maintaining cultural identity and healthy lifestyles. The current research took a community-engaged approach to evaluate an urban AI youth after-school program that has transitioned into a culturally grounded prevention program. Ways to create a successful research collaboration between AI communities and academics is discussed as well as implications for understanding the importance of culturally-grounded programs for AI youth who resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…This finding is congruent with the philosophy of culture as prevention/treatment, which asserts that connection to or immersion in Indigenous culture has health-promoting impacts for Indigenous people and communities. In short, "culture is a social determinant of mental health/well-being for Indigenous/Native peoples" [61]. Connection and identity represent the foundation for the profound impacts of culture, which was precisely what this program worked to restore and strengthen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is congruent with the philosophy of culture as prevention/treatment, which asserts that connection to or immersion in Indigenous culture has health-promoting impacts for Indigenous people and communities. In short, "culture is a social determinant of mental health/well-being for Indigenous/Native peoples" [61]. Connection and identity represent the foundation for the profound impacts of culture, which was precisely what this program worked to restore and strengthen.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is time to elevate Indigenous knowledge and principles of health and well-being into health care delivery. In fact, Indigenous culture within medical settings is acceptable to healthcare professionals [79], is cost-effective [80], and is more effective than Western care alone for addressing health care risks amongst Indigenous populations [60,61]. Given this information coupled with the knowledge of the deep disparities that exist for Indigenous versus non-Indigenous communities on many health indicators, it is medically neglectful to not utilize Indigenous culture and community in all healthcare interventions with this population.…”
Section: Discussionmentioning
confidence: 99%
“…Participants found strength in family relationships, spirituality, helping others, and coming together as a cultural community. A similar study conducted by Masotti et al (2020) in California measured culture in 3 sub-scales: Identity, traditions, and spirituality. This study demonstrated a definite link between cultural connectedness, mental health, and well-being using hope measures, concluding that culture is a strong social determinant of positive mental health and well-being for Indigenous Native groups in the United States.…”
Section: Culturementioning
confidence: 99%
“…Peters et al, developed the Wicozani instrument (9 items) as an Indigenous measure of ‘overall health and well-being’ [ 17 ], and Walls et al, developed a ‘social-cultural integration’ measure [ 18 ]. In addition to these, King et al, (2019) and Masotti et al, (2020) adapted and validated the Canadian Cultural Connectedness Scale for use in an urban dwelling diasporic Native/Indigenous California community [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Issues identified included: i) the lack of culturally informed methods to evaluate, from an Indigenous/Native perspective, the positive outcomes of culture-based programs to improve health and well-being; and ii) interest in providing an approach that recognized the relationship between Native American/Indigenous culture and health [ 19 , 20 ]. The Culture is Prevention Project evolved into a 6-phased community-based participatory research (CBPR) program (See Table 1 ).…”
Section: Introductionmentioning
confidence: 99%